Between Planets - Heinlein Robert 19071988; Geary, Clifford N. (New York, Scribner, 1973)
When war threatens to break out between Venus and Earth, a boy with citizenship on both planets, attending school on Earth but whose home is on Mars, finds himself in an awkward situation.
Keywords: Science fiction; Science fiction